Second Malignancy Risk in Patients with Bronchopulmonary Carcinoids: Epidemiological Results from Italian Network of Cancer Registries. Issue 2 (March 2017) - Lococo, Filippo; Galeone, Carla; Sacchettini, Claudio; Leuzzi, Giovanni; Cesario, Alfredo; Paci, Massimiliano; Mangone, Lucia; ,
Purpose: This epidemiological study aimed to determine the prevalence and characteristics of second tumors (STs) in patients with bronchopulmonary carcinoids (BCs). Methods: Data on neuroendocrine carcinomas (NECs) from the AIRTUM registry (1975-2011) were used for the analysis. Among 32, 325 NECs, we focused our analysis on 3, 205 patients (9.9%) affected by BCs. The overall ST number and incidence were calculated. The number of STs was compared with the expected cancer number in the healthy Italian population, and the standardized incidence ratio (SIR) and 95% confidence intervals were calculated. Results: The male/female ratio was 1.5:1 and the mean age 61.7 years (range: 7-94). A total of 640 STs were observed (overall incidence: 20%): 198 tumors were metachronous, 23 synchronous, and 419 occurred before the diagnosis of BC. The most common STs were bladder tumors (12.2%) followed by breast tumors (11.1%). We observed a large number of thyroid tumors (SIR = 3.88), with a remarkably higher frequency of thyroid tumors being synchronously detected with BC in female patients (SIR = 61.39). In male patients there was an increased frequency of urinary system tumors, in particular metachronous tumors of the kidney and renal pelvis (SIR = 3.34) and synchronous tumors of the urinary bladder (SIR = 11.48). Conclusions: A high frequency of STs is predictable in patients with BCs, with synchronous thyroid tumors being observed in women and kidney and urinary bladder tumors in men. However, these data should be interpreted with caution, considering that the diagnosis of such tumors often occurs as an incidental finding during investigations for other malignancies.